(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
One of the primary goals of the curriculum is to help students gain the necessary skills andinformation. The ability to think critically is viewed as a necessary talent for the 21st century and shouldbe taught in schools. However, the key difficulty is how to teach thinking or critical thinking and how toget pupils to reflect on their own thinking methods. An significant aspect in terms of education systemsand curricula is that critical thinking cannot be learned from a textbook, but rather sparked in the mind.Teaching critical thinking is not just about teaching kids how to think, but also educating their brainsto be flexible and active enough to think about, research, and analyse new and old information or factsthat they are exposed to. In this paper discuss the Primary school teacher to educate critical thinking.